The large perpendicular magnetic anisotropy induced at the Co2FeAl/MgAl2O4 interface and tuned with the strain, voltage and charge doping by first principles study. (14th September 2021) - Cheng, Ming; Zhang, Zhenhua; Yuan, Xiaojuan; Liu, Yong; Lu, Zhihong; Xiong, Rui; Shi, Jing
Abstract: The heterostructures with high perpendicular magnetic anisotropy (PMA) have advantages for the application of the nonvolatile memories with long data retention time and small size. The interface structure and magnetic anisotropy energy (MAE) of Co2 FeAl/MgAl2 O4 heterostructures were studied by first principles calculations. The stable interface atomic arrangement is the Co or FeAl layer located above the equatorial oxygen coordinate in the distorted oxygen octahedrons. The Co–O interface can induce large effective PMA up to 4.54 mJ m −2, but this structure is a metastable structure. Meanwhile, the effective MAE decreases linearly as the thickness of the ferromagnetic layer increase. The effective MAE for the FeAl–O interface is only 1.3 mJ m −2, while the maximum thickness of Co2 FeAl layer that maintains the PMA effect is about 1.717 nm. These values are very close to the experimental results. Through d -orbital-resolved MAE, we confirm that the interface PMA is mainly originated from the hybridization between d x y, d y z and d z 2 orbitals of interface 3 d atoms. In addition, the compressive strain, negative electric field and hole doping can significantly enhance the effective PMA of FeAl–O interface. At the same time, Co–O interface will become the most stable structure by tuning the Mg/Al ratio in the spinel layers. The large effective PMA makes the Co2 FeAl/MgAl2 O4 junction a perfect candidate for the next-generation of non-volatile spintronic devices.